The Effectiveness of Peppa Pig Cartoon Film in Enhancing Vocabulary Mastery Among Seventh-Grade Students - Cahyani, Utari Nur; Lestari, Yuni Budi (LITPAM, 2026)
This study aimed to examine the effectiveness of using Peppa Pig cartoon in enhancing vocabulary mastery among seventh-grade students of SMP Negeri 21 Mataram. A quasi-experimental design with non-equivalent control groups was employed involving 28 students divided into experimental (n=14) and control (n=14) groups. The intervention consisted of four 40-minute sessions over two weeks. Data were collected through pre-test and post-test instruments measuring receptive vocabulary knowledge of verbs and adjectives. Data were normally distributed and homogeneous. The experimental group received instruction using Peppa Pig episodes, while the control group was taught using traditional methods. Descriptive analysis showed that the experimental group's mean score increased from 57.50 (pre-test) to 67.00 (post-test), whereas the control group's mean slightly decreased from 54.29 to 52.86. The independent sample t-test revealed a statistically significant difference between the two groups (t (26) = -2.281, p = 0.031, p < 0.05) with a large effect size (Cohen's d = 0.86). The null hypothesis was rejected, and the alternative hypothesis was accepted. Unlike previous studies focusing on general cartoons or young children, this research specifically investigates Peppa Pig as a targeted pedagogical tool for early adolescents in a quasi-experimental controlled setting. The Peppa Pig cartoon is effective in enhancing vocabulary mastery among seventh-grade students and can be integrated into English language instruction as an engaging, multimodal learning medium.